Factors Related to Exclusive Breastfeeding at Posyandu Margamulya, Mauk District - Rachmayanti S, Tami (STIKes RSPAD RSPAD Gatot Soebroto, 2024)
The purpose of this study was to determine the factor associated with exclusive breastfeeding at posyandu margamulya, mauk district. This study used a quantitative research design with cross sectional method. The population of this study were mothers who had babies aged 0-6 months. The samping technique used total sampling with a number of respondents 43 people. Data collection tools using questionnaire abd checklists. The results showed that the majority of mothers did not exclusively breastfeed, amounting to 26 mothers (60,5%), based on the age of the majority of mothers aged 20-35 years amounted to 20 mothers (46,5%), based on education, the majority of mothers with low education were 27 mothers (62,8%), based on work, the majority og working mothers are 30 mothers (69,8%), based on parity, the majority of primiparous mothers were 25 mothers (58,1%), based on knowledge the majority of mothers have sufficient knowledge of 20 mothers (46,5%), based on husband’s support, amounting to 23 mothers (53,5%). The results of statistical tests with kai squared of 6 variabels all have a relationship with exclusive breastfeeding. Based on the results of the research, the suggestion put forward is that mothers at the margamulya posyandu are expected to further improve their ability to maintain the health of their babies through exclusive breastfeeding and their husband’s motivation is needed to support the mothers in giving exclusive breastfeeding.